Analisis Yuridis dan Pandangan Hukum Pidana Islam Anak yang Membawa Senjata Tajam untuk Aksi Tawuran - Wahyu Shuhada; Ramadhan Syahmedi Siregar (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Sharp weapons are very useful and necessary in terms of arming oneself or defending or defending oneself from things that threaten the soul, but if misused or used is not in accordance with applicable laws and regulations, this research using normative legal research does not recognize field research ( field research) because what is being studied is legal materials so that it can be said to be library based, focusing on reading and analysis of the primary and secondary material. This research will then draw a conclusion regarding Juridical Analysis and Islamic Criminal Law Views of Children Carrying Sharp Weapons for Fighting Actions on a decision study (Number 70/Pid.Sus-Children/2022/PN Mdn). In Indonesia, the use of sharp weapons without rights and without permission is strictly prohibited because it can injure other people, therefore the State of Indonesia makes rules that prohibit its people fortunately not to carry or use sharp weapons carelessly which is contained in the Emergency Law of the Republic of Indonesia number 12 of 1951 Article 2 paragraphs 1 and 2. According to Islamic law there is no normative argument regarding criminal sanctions, especially in the form of imprisonment, because criminal sanctions against children in Islam are ta'dib (education) which are handed over to the waliyul amri (leader) Keywords: Children, sharp weapons, crime